Faktor–Faktor yang Mempengaruhi Pendapatan Usahatani Padi dan Kontribusinya terhadap Pendapatan Rumah Tangga di Pliken - Fio Sofianita; Herman Sambodo; Istiqomah Istiqomah (J-MAS (Jurnal Manajemen dan Sains), 2022)
The agricultural sector, especially rice farming, has a very important role for the Indonesian population. In addition, related to the issue of Indonesian food security, the sector also has a very large influence on the community because most of the Indonesian population earns income from the agricultural sector and not a few who depend on the sector for their livelihood. The purpose of this study were to analyze the effect of age, education level, farming experience, land area, and harvesting system on rice farming income measure the contribution of rice farming income to household income, and measure the living feasibility of farmers by comparing the income of rice farming with the UMK. The data collection technique is using the interview method based on a questionnaire while the analysis technique uses multiple linear regression. The result of this research is that the variables of education, land area and harvesting system have an effect on rice farming income, while the variables of age and farming experience have no effect. Average contribution of rice farming income to household income is still low. Farmers are included in the category of not living properly because their income from rice farming is still below the UMK.